CONSEQUENCES IMPLEMENTASI TOTAL QUALITY MANAGEMENT - Rovilla El Maghfiroh; Eko Afriyanto (Universitas Hayam Wuruk Perbanas, 2011)
This study is aimed to prove and analyze the effect of focus on the custometi continuous improvement process, and integrated involvement, productive behavior of employee, pedormance of employee. As population are 140 respondents. This study employed complete enumeration or census method; hence, sample and sampling technique were not required. The technical analysis applied to test the research hypothesis was multiple regressions. The results of this research show that tltere are positive and significant relationship between Subsystems of TQM consisls of afocus on the customer, continuous improvement process, and integrated involvement, productive behavior of employee, performance of employee. Benefit of this research can be used as scientific information regarding the variables of between Subsystems of TQM consists of afocus on the customer continuous improvement process, and integrated involvement, productive behavior of employee, performance of ernployee.